2010
DOI: 10.1158/1078-0432.ccr-09-3100
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Anti-VEGF Treatment Duration on Tumor Growth, Tumor Regrowth, and Treatment Efficacy

Abstract: Purpose: Inhibition of the vascular endothelial growth factor (VEGF) axis is the basis of all currently approved antiangiogenic therapies. In preclinical models, anti-VEGF blocking antibodies have shown broad efficacy that is dependent on both tumor context and treatment duration. We aimed to characterize this activity and to evaluate the effects of discontinuation of treatment on the dynamics of tumor regrowth. Experimental Design: We evaluated the effects of anti-VEGF treatment on tumor growth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
105
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(114 citation statements)
references
References 46 publications
4
105
0
5
Order By: Relevance
“…However, whether tumor regrowth occurs after discontinuation of antiangiogenic therapy is controversial. Results from a study using various different cell lines indicate that tumors that relapsed after cessation of therapy did not grow faster compared with untreated tumors (46). However, most of this work was done by injecting cancer cells subcutaneously where tumor-related angiogenesis is highly different from that at orthotopic sites (47).…”
Section: Discussionmentioning
confidence: 99%
“…However, whether tumor regrowth occurs after discontinuation of antiangiogenic therapy is controversial. Results from a study using various different cell lines indicate that tumors that relapsed after cessation of therapy did not grow faster compared with untreated tumors (46). However, most of this work was done by injecting cancer cells subcutaneously where tumor-related angiogenesis is highly different from that at orthotopic sites (47).…”
Section: Discussionmentioning
confidence: 99%
“…Select mice received anti-VEGF at a dose of 10 mg/kg 24 hours before dosing radiolabeled trastuzumab or its control mAb. The dose of anti-VEGF mAb was based on previously reported xenograft growth inhibition activity (16,38), whereas the time interval was based on reported statistically significant reductions in vascular density of human xenografts in mice at 24 hours following anti-VEGF administration (28). Furthermore, a pharmacokinetic model simulation indicated that either a 5 mg/kg twice a week or 10 mg/kg weekly dosing regimen would result in a minimum trough concentration at steady state of 30 mg/mL, similar to that achieved in more than 90% of bevacizumab patients (38).…”
Section: Elisamentioning
confidence: 99%
“…However, the optimal duration is unclear and there is a biological rationale to hypothesize a survival benefit from post-progression administrations. [10] The TML and the Bebyp trials investigated protracted administration of bevacizumab after progression to a first-line chemotherapy. Both trials were positive, confirming that protracted administration of bevacizumab, beyond progression, leads to survival advantage.…”
Section: Discussionmentioning
confidence: 99%
“…[9] Some authors have argued that, since resistance is established, the sudden suspension of the antiangiogenic drug can rapidly increase blood vessels formation, with more pronounced angiogenesis and faster prog ression, sug gesting possible benefits from longer treatment durations. [10] Recently, two randomized trials investigated the administration of bevacizumab beyond progression. [11,12] In these studies, patients progressed after the failure of a bevacizumabbased first line chemotherapy were randomized to continuation or suspension of bevacizumab.…”
Section: Introductionmentioning
confidence: 99%